PERAN ORANG TUA DALAM MEMBANTU PERKEMBANGAN DIRI ANAK AUTISME - Nisa Hermawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2008)
No one in this world wants to have an abnormal child. All parents want their children normal. In fact, some of them have are not, for example autistic child. Autism is a rare developmental disorder involving inability to communicate with respond to other people. Therefore, it is parents’ role to help autistic child in order to develop social and language skill. In helping autistic child parents must cooperate with experts by giving them information of their child.